Growth and volatility of tax revenues in Latin America - Hans Fricke; Bernd Süssmuth (Center for Economic Studies and ifo Institute (CESifo), 2011)
Against the background of a notoriously high macroeconomic instability and the need to raise tax revenues to meet the demands of public spending, this paper analyzes the tradeoff between growth and volatility of tax revenues in Latin America. We use a two-step Engle-Granger-type model to estimate short-run and long-run elasticities, accounting for statedependentasymmetric reactions of short-run elasticities over the business cycle. Due to its dependence on commodities exploitation Latin America is in general susceptible to the boombust cycles of its natural riches. Controlling for the composition of revenue sources and other idiosyncrasies of Latin American economies, we find revenues above (below) its long-run equilibrium to react stronger (weaker) to business cycle dynamics. This 'tax revenue channel' represents an indirect argument for counter-cyclical discretionary fiscal policy in the region. Our detailed elasticity estimates can give some orientation on how to reach necessary higher tax levels without creating disincentives and inequities through business cycle instabilities on the way to develop an adequate internal tax system.
Keywords: H20; O10; E60; 330; tax policy; developing countries; regime-dependent elasticity; Steuerpolitik; Steueraufkommen; Elastizität; Wirtschaftswachstum; Entwicklungsländer; Lateinamerika